2001
DOI: 10.1590/s0100-29452001000200023
|View full text |Cite
|
Sign up to set email alerts
|

FITOTOXICIDADE DE FUNGICIDAS, ACARICIDAS E INSETICIDAS, SOBRE O MAMOEIRO (Carica papaya L.) CULTIVAR SUNRISE SOLO IMPROVED LINE 72/12 EM CONDIÇÕES DE CAMPO

Abstract: A presente pesquisa teve como objetivo estudar os efeitos fitotóxicos de fungicidas, acaricidas e inseticidas e algumas associações entre eles, em plantas de mamoeiros (Carica papaya L.) cv. Sunrise Solo Improved Line 72/12, em condições de campo, no município de São Mateus -- ES, pertencente à maior região produtora do Estado. O experimento foi arranjado em delineamento de blocos casualizados, com 4 repetições e 03 plantas úteis por parcela. Foram utilizados os seguintes produtos, com as respectivas doses, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In both experiments, plants were sprayed with the tested lime sulfur concentrations using a costal sprayer Brudden® SS model with a capacity of 5 L. Visual symptoms of phytotoxicity for each concentration tested were evaluated by two observers after 1, 5 and 10 days of treatment. A visual scale of phytotoxicity was used: rank 0: plants with normal leaves and no signs of burns; rank 1: plants with slightly damaged leaves and/or with small burned areas; rank 2: plants with medium damaged leaves, yellow with burnt edges and tips; rank 3: plants with heavily damaged leaves, showing severe defoliation.…”
Section: Methodsmentioning
confidence: 99%
“…In both experiments, plants were sprayed with the tested lime sulfur concentrations using a costal sprayer Brudden® SS model with a capacity of 5 L. Visual symptoms of phytotoxicity for each concentration tested were evaluated by two observers after 1, 5 and 10 days of treatment. A visual scale of phytotoxicity was used: rank 0: plants with normal leaves and no signs of burns; rank 1: plants with slightly damaged leaves and/or with small burned areas; rank 2: plants with medium damaged leaves, yellow with burnt edges and tips; rank 3: plants with heavily damaged leaves, showing severe defoliation.…”
Section: Methodsmentioning
confidence: 99%
“…The visual scale of phytotoxicity proposed by Vieira et al (2001) was used, with 0: plants with normal leaves and no signs of burns; 1: plants with slightly damaged leaves and/or with small burned areas; 2: plants with medium damaged leaves, yellow with burnt edges and tips; 3: plants with heavily damaged leaves, showing severe defoliation.…”
Section: Control Of T Evansi In the Greenhousementioning
confidence: 99%
“…However, Silva et al [17], evaluating the effects of soybean seed treatments 28 days after emergence, found that the treatment with abamectin positively affected plant height, shoot dry matter, and root volume compared to the control (with no seed treatment). Studies with other crops, such as papaya (Carica papaya L.) [75] and tomato (Solanum lycopersicum L.) [76], did not report the phytotoxic effects of abamectin treatment as a strategy for nematode control.…”
Section: Discussionmentioning
confidence: 99%